(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Good packaging and eminence product that matches the price over and over again calls for recurring patronage from consumers which allow the firm to hang about in business. Attractive packaging of products creates voluntarily available market for the firm and may reduce on advertising cost. This study examines the result of good packaging of products on consumers buying alternative as well as on impulse buying. Data were obtained from the supervision of 100 copies of a structured questionnaire to consumers who come for shopping at market places, supermarkets and high traffic points across the Punjab using deliberate sampling technique. The test results revealed that 79 and 81% of consumers decision to purchase a particular product as well as impulse buying was accounted for by the packaging approach of the product, while the chi-square results indicated that attractive packaging inclined consumers buying choice and impulse buying (p>0.05).